Walkability around primary schools and area deprivation across Scotland - Laura Macdonald; Paul McCrorie; Natalie Nicholls; Anne Ellaway (BMC, 2016)
Abstract Background A number of studies based in the US, Canada, and Australia, have found evidence of associations between the built environment (BE) and mode of transport to school, and links between active travel and deprivation. Limited research in the UK compares potential BE supports for walking to school by area deprivation. Within this study, we gathered data on BE attributes previously linked to active travel, i.e., street/path connectivity, and dwelling density, created a composite 'walkability score' (WS) for areas around primary schools across urban Scotland, and explored whether poorer areas exhibit lower scores than more affluent areas, or vice versa. We consider this to be a novel approach as few studies have compared BE features by deprivation across a whole country. Methods Address and road/path maps were obtained and primary schools (N = 937) across mainland Scotland were mapped. Schools were attributed income deprivation scores (scores divided into quintiles (Q1: least deprived, Q5: most deprived)). Catchment area (CA) boundaries, i.e., the geographic area representing eligibility for local school attendance, were drawn around schools, and WS calculated for each CA. We compared mean WS by income quintile (ANOVA), for all local authorities (LAs) combined (N = 29), and separately for the four LAs with the greatest number of schools included in the analysis. Results For all LAs combined, the least deprived quintile (Q1) showed a significantly lower WS (−0.61), than quintiles 3, 4 and 5 (Q2: −0.04 (non-sig), Q3: 0.38, Q4: 0.09, Q5: 0.18); while for Glasgow the second least deprived quintile (Q2) showed significantly higher WS (Q1: 1.35, Q2: 1.73), than middling (Q3: 0.18) and most deprived quintiles (Q4: 0.06, Q5: −0.10). Conclusion WS differ by deprivation with patterns varying depending on the spatial scale of the analysis. It is essential that less walkable areas are provided with the resources to improve opportunities to engage in active travel.